Justice and beneficence. Issue 5 (2nd September 2016) - Gilabert, Pablo
Abstract : What is a duty of justice? And how is it different from a duty of beneficence? We need a clear account of the contrast. Unfortunately, there is no consensus in the philosophical literature as to how to characterize it. Different articulations of it have been provided, but it is hard to identify a common core that is invariant across them. In this paper, I propose an account of how to understand duties of justice, explain how it contrasts with several proposals as to how to distinguish justice and beneficence, respond to some objections, and suggest further elaborations of it. The conceptual exploration pursued in this paper has practical stakes. A central aim is to propose and defend a capacious concept of justice that makes a direct discussion of important demands of justice (domestic and global) possible. Duties of justice can be positive besides negative, they can be imperfect as well as perfect, they can range over personal besides institutional contexts, they can include multiple associative reasons such us non-domination, non-exploitation, and reciprocity, and they can even go beyond existing national, political, and economic associative frameworks to embrace strictly universal humanist concerns. We should reject ideological abridgments of the concept of justice that render these possibilities, and the important human interests and claims they may foster, invisible.